Lulo (Solanum quitoense Lamarck.) as a new element of the landscape in Mexico: germination and growth on organic substrates - Gómez-Merino, Fernando C.; Trejo-Téllez, Libia I.; García-Albarado, J. Cruz; Morales-Ramos, Victorino (Revista Mexicana de Ciencias Agrícolas, 2018)
We evaluated three different combinations of cachasa compost and peat (T1 40:60 T2 60:40; T3, 80:20, corresponding to relations peat: compost of 1.50, 0.66 and 0.25) on seed germination and seedling growth of lulo (Solanum quitoense Lamarck.), a species that has potential as a landscape element in coffee agroecosystems in Mexico. The research was conducted in the greenhouse with shade cloth during the months of October and November 2012 at an elevation of 650 masl, at 18° 50” north latitude and 96° 51" W, in a place with 18.4 °C annual average temperature and 78% Relative Humidity. The experimental design was completely randomized with four replications. Comparison of means was done by Tukey test (p≤ 0.05). The highest percentage of seed germination and increased root development was observed in the treatment T3 (80% compost; relationship peat: compost of 0.25), although this treatment also recorded lower plant height, stem diameter, size leaves and SPAD units. Higher average values in plant height, stem diameter, length and width of leaves were recorded in T1 and T2 (p≤ 0.05). Lulo seeds can germinate and produce healthy seedlings exposed to experimental conditions in relations peat: compost between 1.50 and 0.66, corresponding to 40 and 60% compost in the substrate, while the relationship peat: compost of 0.25 increases seedling germination but produces lower quality for transplantation.
Keywords: Solanaceae; agroecosystems; andean fruits; compost; peat